Laser Shock‐Induced Polycrystallization Engineering for Plasmon Damping Tuning of Metallic Nanoparticles. Issue 3 (8th December 2022) - He, Yali; Liu, Jian; Hu, Yizhong; Hu, Yaowu
Abstract: Currently, lattice defect engineering provides an effective route for plasmon damping adjustment. To address the low efficiency of defect introduction in nanoparticles, a laser shock‐induced polycrystallization strategy is proposed. The results demonstrate that Au nanoparticles undergoing the ultrahigh‐strain‐rate compression process exhibit effective grain boundary defect introduction and plasmonic damping tuning effects. The size dependence of the polycrystallization process and plasticity mechanism of nanoparticles are comprehensively explored. The correlation between the optical properties and microstructure of the deformed nanoparticles is established. The proposed process provides a facile strategy for optical loss tuning and complements the plastic deformation mechanism of plasmonic nanoparticles in extreme deformations. Abstract : A laser shock‐induced polycrystallization strategy is proposed to enable an excellent lattice defect introduction effect and plasmon damping tuning effects of nanoparticles. The size dependence of the polycrystallization process and the polycrystallization mechanism of nanoparticles are comprehensively explored. The correlation between the optical properties and microstructure of the deformed nanoparticles is established.